Telling One's Story: Understanding Healing as it is Conveyed in the Memoirs of Childhood Sexual Abuse Survivors - Martin, Stephanie (2014)
The purpose of the current study is to better understand the experience of healing after childhood sexual abuse (CSA) through analysis of existing survivor narratives. Traditionally, study of CSA survivors has been approached from a point of view that categorizes their response to abuse a deficit or disorder. A recent movement in the study of CSA has been toward viewing CSA survivors in terms of resilience and healing. The current research study is informed from the social constructivist paradigm, and uses narrative and hermeneutics to gain a better understanding of healing from CSA by examining existing narratives of healing written by survivors. The method of narrative analysis employed is Lieblich Tuval-Mashiach & Zilber’s (1998) holistic-content approach. After interpreting each individual narrative, an overarching analysis was generated by interpretation of commonalities across memoirs. The narratives and my subsequent analysis of the narratives generated a storied construction of healing, organized into three themes: The Process of Transformation, From the Private to the Public, and Connecting to Others. The results are discussed in light of the socio-cultural and political landscapes, as well as in terms of the concept of self-compassion. Strengths and limitations of the study, as well as considerations for future research are considered